2018
DOI: 10.1007/s40264-018-0639-1
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Perforations with Biologics in Patients with Rheumatoid Arthritis: Implications for Clinicians

Abstract: Gastrointestinal (GI) perforations are rare events in rheumatoid arthritis (RA) patients, but cause significant morbidity and mortality. Several studies indicate that RA patients may be at higher risk of GI perforation. Traditional RA treatments such as glucocorticoids and non-steroidal anti-inflammatory drugs increase the risk of perforation. In the past two decades, a new class of therapeutic agents called biologics has been added to the RA treatment armamentarium. Biologics are effective in controlling dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
1
20
1
1
Order By: Relevance
“…Unlike previous sirukumab trials in RA [31,32,37], no gastrointestinal perforations, a known consequence of anti-IL-6 therapies [39], were reported in the current study; and there were no reported deaths or tuberculosis re-activations. Two patients receiving sirukumab had visual disturbances considered potentially GCA related.…”
Section: Discussioncontrasting
confidence: 83%
“…Unlike previous sirukumab trials in RA [31,32,37], no gastrointestinal perforations, a known consequence of anti-IL-6 therapies [39], were reported in the current study; and there were no reported deaths or tuberculosis re-activations. Two patients receiving sirukumab had visual disturbances considered potentially GCA related.…”
Section: Discussioncontrasting
confidence: 83%
“…Data on other non-TNFi bDMARDs and comparisons between bDMARDs is limited, 12 but available data suggests a possibly increased risk of lower GI perforations associated with tocilizumab. A safety signal was first triggered by several cases reported in preapproval clinical trials and postmarketing surveillance for tocilizumab.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, one large analysis of data from the British Society for Rheumatology Biologics Register found no difference in risk, comparing tumour necrosis factor inhibitor (TNFi) versus csDMARDs, after adjusting for GC use and other risk factors. 11 Data on other non-TNFi bDMARDs and comparisons between bDMARDs is limited, 12 but available data suggests a possibly increased risk of lower GI perforations associated with tocilizumab. A safety signal was first triggered by several cases reported in preapproval clinical trials and postmarketing surveillance for tocilizumab.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 As the effect of TCZ, although the exact mechanism of GI perforations due to IL-6 receptor blockade is not yet understood, it is thought they may be associated with the effects of IL-6 inhibition on vascular endothelial growth factor (VEGF). 11 VEGF plays an important role in maintaining the integrity of the intestinal mucosa in intestinal damage caused by acute or chronic processes, and it is a targeted cytokines in many cancer treatments as it is highly effective during angiogenesis. 12 Similar to TCZ, clinical studies have shown that drugs with active substance of bevacizumab, another VEGF inhibitor, are also associated with GI perforations.…”
Section: Discussionmentioning
confidence: 99%
“…13 Therefore, a decrease in VEGF levels may increase the risk of GI perforation. 11 Especially in the treatment of elderly RA patients with a history of diverticulitis, the use of these drugs should be paid attention; likewise, the use of TCZ alone in patients with a history of diverticulitis increases the risk of lower GI perforation. 10,14 In ancient times, GI complications were among the most common causes of death in patients diagnosed with RA.…”
Section: Discussionmentioning
confidence: 99%